The Revitalization of “Aek Sipitu Dai” Batak Toba Folklore into Teaching Materials in English Subject for Junior High School - Desy Linda Sihombing; Bambang Nur Alamsyah Lubis; Analisa Simbolon; Fitri Pebrini Simamora (English Teaching and Linguistics Journal (ETLiJ), 2021)
This study aimed to inform the capability the folklore of Aek Sipitu Dai into learning materials at Junior High School. The objective of the studies were to develope Aek Sipitu Dai Batak Toba Folklore into teaching materials in English subject for Junior High School, to transcribe Aek Sipitu Dai Batak Toba Folklore into teaching materials in English subject for Junior High School, to refresh Aek Sipitu Dai Batak Toba Folklore into teaching materials in English subject for Junior High School. This study used descriptive qualitative approach in analyzing the data. The data of this research are interview in observation in Samosir Island. The result of this study, there are a complete story about Aek Sipitu Dai that can be used as teaching materials in English Subject, the complete story are able to be transcribe as a complete story, there was found a Batak Toba Folklore that can be used as teaching material in English Subject